Tranexamic acid and international ambulance services. (2nd June 2020) - Spaans, Adam; Martin, Jake; Ebbs, Phillip
Abstract : Introduction: Severe haemorrhage may lead to pathologic release of fibrinolytic enzymes, which break down blood clots. Tranexamic acid (TXA) is a drug that inhibits the fibrinolysis of blood clots. Aim: The purpose of this review is to explore current literature regarding prehospital TXA administration for patients suffering severe haemorrhage following trauma, and to discuss whether this drug should be more widely used across modern international ambulance services. Methods: Literature searches of EBSCO Host, ProQuest and PubMed databases were conducted in August, 2019. Results: TXA administration within 3 hours following injury is associated with improved outcomes for severe haemorrhage patients. However, there are reservations that the success of TXA in developing countries and military settings may not be directly transferrable to the modern civilian healthcare systems. Discussion: The benefits of prehospital TXA administration appear compelling. Further studies will help guide wider international implementation of this drug in paramedic practice.